Occupational Therapy 's Work and Industry Area of Practice: Content in Entry-Level Professional Occupational Therapy Curricula: A Survey - Thomas F. Fisher (Scholarworks @ WMU, 2019)
The Occupational Therapy Practice Framework: Domain and Process identifies work as an area of occupation that has long been recognized by the profession as an area of practice. This study identified how entry-level professional occupational therapy programs meet educational standards required by the Accreditation Council for Occupational Therapy Education for educational programs. Standards identified were those that relate to the area of work and industry practice. One hundred and sixty-seven program directors were invited to participate in a survey directed at work and industry occupational therapy practice. Items on the survey related to content taught in their entry-level occupational therapy programs. Sixty-eight programs (47%) participated. The results showed 40 out of 68 respondents (58.82%) indicated not enough time spent on work and industry content in their curriculum. No respondents indicated too much time is spent on this content. The other 41.18% reported there was enough time for this content in their curricula. It is important that work and industry content is adequately covered in the curricula of entry-level occupational therapy professional programs to prepare students for this area of practice. This study provides a foundation for future research related to professional occupational therapy education as it relates to work and industry practice.